The Functions of Major Gut Microbiota in Obesity and Type 2 Diabetes - Siman Liu; Zhipeng Tao; Mingyu Qiao; Limin Shi (Metabolites)
Background: Gut microbiomes play a vital role in maintaining whole-body metabolic homeostasis. It has gained significant attention in recent years due to advancements in genome sequencing technologies and a deeper understanding of its relationship with obesity. However, the specific ways in which different microorganisms directly or indirectly influence host obesity, as well as the underlying mechanisms, remain uncertain because of the complexity of gut microbiota composition. Methods: In this review, we summarize the roles of the major gut microbiota phyla such as Bacteroidetes, Firmicutes, Proteobacteria, and Verrucomicrobia in obesity and type 2 diabetes based on studies published in the past five years on PubMed and Google Scholar. The current therapeutic strategies associated with gut microbiota are also explored from clinical trials, and challenges and future directions are discussed. Results and Conclusions: This review will provide a deeper understanding of the functions of major gut microbiota in obesity and type 2 diabetes, which could lead to more individualized and effective treatments for metabolic diseases.